Novel supramolecular organogel nanotubular template approach for conducting nanomaterials - Anilkumar, P.; Jayakannan, M. (Journal of Physical Chemistry B, 2010)
We report a unique supramolecular organogel template approach for conducting polyaniline nanomaterials. A novel organogel based on sulfonic acid dopant was designed and developed from renewable resource 3-pentadecyl phenol via ring-opening of 1,4-butane sultone. The amphiphilic dopant molecule formed thermo-reversible supramolecular organogel in highly polar solvents like alcohols. The self-assembled fibril network morphology of the gel was confirmed by scanning electron microscopy (SEM) and atomic force microscopy. Transmission electron microscopy (TEM) revealed that the inner part of the fibrous gel is nanotubular with the pore diameter of similar to 75 run. The organogel nanotubular morphology was retained even in the presence of aniline+dopant complex, and the aniline monomers occupied the hydrophobic nanopockets provided by the amphiphilic dopant. The chemical oxidative polymerization of the dopant+aniline organogel template produced well-defined polyaniline nanofibers. The polymerization was carried out at various temperatures to establish the role of the physical state and stability of the organogel on the morphology. The sulfonic acid molecule acts both as self-assembled molecular template for the synthesis of polymer nanomaterial as well as anionic counterpart for stabilizing the positively charged conducting polymer chains. The gel template played a pivotal role in directing polyaniline chains to form nanofibers and also manipulating the number of other properties such as conductivity, solubility, percent crystallinity, and solid-state ordering, etc. Temperature-dependent electrical conductivity measurements revealed that the nanomaterials showed typical linear ohmic behavior and also followed the 3-D VRH model at elevated temperatures.